Kajian Theileiriosis pada Sapi Di Kabupaten Pohuwato - Tri Ananda Erwin Nugroho; Muhammad Sayuti; Elvin Amuda (Florea : Jurnal Biologi dan Pembelajarannya, 2022)
Blood parasites such as Babesia, Theileria, Trypanosoma and Anaplasma are disease agents that have a predilection for cattle blood which can cause losses in the cattle breeding sector. This study aims to conduct a study of Theileiriosis in cattle in Pohuwato District. Sampling of cattle blood was carried out proportionally in 13 sub-districts in Pohuwato Regency with a total of 100 samples from a total population of 29,266 cattle. Blood samples were taken through the jugular vein. Examination of the samples used the thin blood smear method with Giemsa staining and observed with a 1000 magnification microscope. The incidence rate of Theileiriosis was determined by counting the number of positive blood samples infected with Theileria sp., divided by the total number of samples examined multiplied by one hundred percent and then the data were analyzed descriptively. Based on the results of the study, of the 100 blood samples examined, 31 blood samples were found Theileria sp., in the observed blood smear preparations. The incidence rate of Theileiriosis in cattle in Pohuwato District is 31%.